Update on thiol status and supplements in physical exercise - Sen, C. K. (Canadian Journal of Applied Physiology, 2001)
Strenuous physical exercise represents a condition that is often associated with increased production of reactive oxygen species in various tissues. One of the most reliable indices of exercise-induced oxidant production is tissue glutathione oxidation. In humans, exercise-induced blood glutathione oxidation is rapid and subject to control by antioxidant supplementation. The objective of this brief review is to provide an update of our current understanding of cellular thiols and thiol antioxidants. Cellular thiols are critically important in maintaining the cellular antioxidant defense network. In addition, thiols play a key role in regulating redox-sensitive signal transduction process. Lipoic acid is a highly promising thiol antioxidant supplement. Recent studies have clarified that while higher levels of oxidants may indeed inflict oxidative damage, oxidants are not necessarily deleterious. Under certain conditions oxidants may function as cellular messengers that regulate a multitude of signal transduction pathways. In light of this, the significance of oxidants in various aspects of biology needs to be revisited.